Depollution of Rivers and Lakes - Santos, A.S.; Bittencourt, C. (European Journal of Sustainable Development, 2017)
The need to control pollution is a relevant environmental issue in Brazil, and in the world. Population growth demands a greater exploitation of natural resources, in many cases, above the natural recovery capacity of ecosystems. The decontamination of a river or lake involves, among other forms of intervention, the management of sanitation services, thus allowing the qualitative improvement of water resources. The progressivity of the supply of sanitation infrastructure will allow the attendance of the regular areas with collection and treatment of sewage. On the other hand, in order to achieve their goals, it is also necessary to address the social issue, the precarious housing, and especially the irregularly settled ones, which demand greater efforts to provide sanitation services. Keywords: Water body. Pollution. Lakes. Rivers